IMPLEMENTATION OF REGIONAL REGULATION NO. 3 OF 2018 ON IMPROVING THE MANAGEMENT OF COLLECTION OF ZAKAT FUNDS - Candri, Kiki; Rahmany, Sri; Hendri, Zul (Al-Infaq: Jurnal Ekonomi Islam, 2023)
This study aims to determine the form of implementation of PERDA Zakat No. 3 of 2018 towards improving the management of zakat funds collection in Bengkalis Regency. The data research methodology in this research is by collecting primary data, namely directly from the sources such as agencies and companies that are the object of research, and the data collection method is by distributing questionnaires. The sampling technique uses nonprobability techniques, namely saturated samples or total sampling, which are census in nature. At the analysis stage, data quality tests, validity tests, reliability tests, classical assumption tests, data normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, and hypothesis tests (T-test and F-test) are carried out. The results of the study show that the PERDA of Zakat in Bengkalis Regency includes 5 aspects, namely Islamic Sharia, Trust, Benefits, Justice, Legal Certainty and Accountability have a significant effect on the management of zakat funds collection in Bengkalis Regency.